let 'er _come_ (1971)
come Directions from the 'skipper' (captain) of the schooner. [PT] _el um_ - steady, hold in position (applies to 'tiller' when steering the boat) _mitchups_ - steady [PT] [PT] let 'er _come_ - come around to the wind let 'er _draw_ - come as you are _hard down_ hard - turn her head to the wind to slow down when getting near land. Yes DICT CEN. Used I Not used Withdrawn Checked by Jordyn Hughes on Tue 05 Jul 2016, NEWFOUNDLAND FOLKLORE SURVEY, [check] beside dictated